Comorbidity: a Modern View on the Problem; Classification (first notice) - Abrahamovych O.; Fayura O.; Abrahamovych U. (Львівський клінічний вісник)
Introduction. Researches of the famous scientists proved, that comorbid diseases often worsen the course of the underlying disease and/or lead to its chronicity, cause disability and premature death of the working population, often make inefficient diagnosis and treatment, increase the costs of the health system to provide medical care. According to the research of WHO experts, people under 40 usually have 2-4 diseases, under 60 – there is a “bouquet” of 5-7 diseases, after 70 – 8-10 or more diseases. So-called “polymorbidity” increases from 10.0 % in patients aged <19 years old to 80.0 % in patients aged >80 years old. Materials and research methods. The work analyzes the literature sources, which deal with the study of comorbid diseases and sufficiently thoroughly reflect the current views of the scientists on the issue. Results of the investigation and their discussion. There are many synonyms of the term “comorbidity”, among them, often are used the following: “polymorbity”, “multimorbidity”, “multifactorial diseases”, “polypathy”, “multicausal diagnosis”, “dual diagnosis”, “pluripathology” etc., which complicates the understanding of the problem and minimizes the ability to use scientific achievements in clinical practice. In Ukrainian literature the authors often use the term “bicausal diagnosis” to describe comorbidity when there are two underlying diseases, to describe polymorbidity – “multicausal diagnosis” (three or more pathological conditions in one individual). In English scientific literature the authors often use the terms “comorbid diseases”, “comorbid conditions”. In general, the sources of information, used by the researchers to study the problem of polypathies, were and are medical histories, hospital records of the patients and other medical records of family doctors, of insurance companies, archives of the pensions for the elderly. Comorbidity itself can be interpreted as a random combination of the diseases, different by its’ etiology and pathogenesis such as nosological syntropy, ie natural occurrence of the regular determined diseases combinations in one patient. The main causes of comorbidity are: affected organs anatomical proximity, common pathogenesis, causal connections, combination of the diseases or iatrogenic causes. Among the factors, that influence the occurrence of comorbidity in humans, is a chronic infection, inflammation, involutive and systemic metabolic changes, iatrogenic factors, social status, environment and genetic predisposition, and the main way of the development of comorbid disorders is causal. The appearing of a particular disease leads to functional first, and later – to organic lesions and further – to an increase of nosologies quantity. Despite the large number of studies, proposed definitions and synonyms, standardized terminology and conventional classification of comorbidity, that would greatly help in the study of its problems, until now is missing. Conclusions. Despite many unsolved patterns of comorbidity and lack of the unified terminology, the search for the new variants of combinations of these diseases continues. After all, they can simply be not yet classified syndromal diseases, or vice versa – to be completely incompatible for the appearance and coexistence in one body. This is the key to solve more and more problems for the diagnosis and treatment of the diseases in the field of the practical medicine.